An investigation into the thermodynamic improvement potential of a transcritical automotive CO2 refrigeration cycle. (5th November 2022) - Song, Xia; Yu, Binbin; Zhang, Yun; Shi, Junye; Chen, Jiangping
Highlights: A simple transcritical automotive CO2 cycle was investigated thermodynamically. A transition from the pseudo-optimal to the optimal high pressure was observed. Significant exergy loss occurred in the throttling process. The evaporator and gas cooler offer significant improvement potential. Abstract: To identify the underlying reasons for the poor efficiency of a transcritical automotive CO2 refrigeration cycle in hot climates clearly, a thermodynamic analysis of ideal and real cycles was performed. The analysis considered energy and exergy (conventional and advanced) viewpoints, determined the ideal cycle efficiency, and identified the improvement potential of each component. Energy analysis results revealed that the ideal efficiency reaches 25.3 at 35 °C outdoor condition, which is far better than currently available real efficiencies. This indicated excellent potential for efficiency improvement. The transition from a pseudo-optimal high pressure under ideal conditions to an optimal high pressure under real conditions occurred upon the emergence of non-ideal factors. Conventional exergy analysis results indicated that exergy destruction within the throttling process accounts for the largest share (36%) of overall exergy destruction. However, advanced exergy analysis results suggested that irreversibilities in the evaporator and gas cooler are the main sources of exogenous exergy destructions in the compressor and throttling process, and their optimization potentials are typically 2–4 times greater than those of compressor and throttling process. Thus, the two heat exchange processes provide significant opportunities for transcritical automotive CO2 refrigeration cycle performance improvement.